Driving under the influence of alcohol and drugs in the eastern part of Denmark in 2015 and 2016: Abuse patterns and trends. (4th July 2018) - Simonsen, Kirsten Wiese; Linnet, Kristian; Rasmussen, Brian Schou
ABSTRACT: Objectives : The objective of this study was to examine the frequency of psychoactive drugs and alcohol in drivers under suspicion of driving under the influence of drugs and alcohol in 2015 and 2016 in the eastern part of Denmark. The trends in the number of traffic cases sent for drug analysis since 2000 and alcohol analysis since 2011 are also discussed. Methods : Blood samples from drivers suspected of being under the influence of alcohol and/or medication and/or illicit drugs in 2015 and 2016 were investigated as requested by the police. The blood samples were screened for alcohol and/or tetrahydrocannabinol (THC) alone, for other drugs (covering all drugs, except THC, listed in the Danish list of narcotic drugs), or for THC and other drugs. Age and gender were also recorded. The number of drug traffic cases since 2000 and the number of alcohol cases since 2011 were extracted from our Laboratory Information Management System (LIMS). Results : In total, 11, 493 traffic cases were investigated. Alcohol and/or drugs exceeded the legal limit in 9, 657 (84%) cases. Men constituted 95% of the drivers investigated for drugs and 88% of the alcohol cases. The drivers investigated for drugs consisted primarily of young men, whereas drivers investigated for alcohol were older. The frequency was higher for positive alcohol cases above the legal limit (87%) than for drug cases (76%) above the fixed concentration limit. THC (67–69%) was the most frequently detected drug above the legal limit, followed by cocaine (27–28.5%), amphetamine (17%), and clonazepam (6–7%) in both years. Morphine (5.4%), included among the 5 most frequent drugs in 2015, was replaced by methadone (4.6%) in 2016. Few new psychoactive drugs (NPS) were detected. The number of traffic cases sent for drug analysis has increased more than 30-fold since 2000–2006, and the number of traffic cases submitted in 2016 for drug analysis was higher than the number for alcohol analysis; the latter has decreased since 2011. Conclusion : Overall, alcohol was the most frequent compound detected above the legal limit in both years, followed by the well-known illicit drugs THC, cocaine, and amphetamine. NPS were seldom seen. One consequence of the increased focus on drugs in traffic has been an immense increase in drug traffic cases sent for analysis since 2006 in the eastern part of Denmark. Although this survey revealed only minimal changes compared to earlier investigations, surveys like this are invaluable for monitoring abuse patterns and trends in drugged and drunken driving.